2010
DOI: 10.1017/s002185961000002x
|View full text |Cite
|
Sign up to set email alerts
|

Application of a model to assess aflatoxin risk in peanuts

Abstract: SU MMARYWhen exposed to hot (22-35 xC) and dry climatic conditions in the field during the final 4-6 weeks of pod filling, peanuts (Arachis hypogaea L.) can accumulate highly carcinogenic and immunosuppressing aflatoxins. Forecasting of the risk posed by these conditions can assist in minimizing preharvest contamination. A model was therefore developed as part of the Agricultural Production Systems Simulator (APSIM) peanut module, which calculated an aflatoxin risk index (ARI) using four temperature response f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 22 publications
1
41
0
2
Order By: Relevance
“…Some attempts regarded also Fusaria (Van Asselt et al, 2012) and A. flavus Chauhan et al, 2015) in maize, while only few studies regard other toxins/crops, e.g. aflatoxins in peanuts (Chauhan et al, 2010) and OTA in grapes (Battilani and Camardo Leggieri, 2015a).…”
Section: Mycotoxins and Producing Fungimentioning
confidence: 99%
“…Some attempts regarded also Fusaria (Van Asselt et al, 2012) and A. flavus Chauhan et al, 2015) in maize, while only few studies regard other toxins/crops, e.g. aflatoxins in peanuts (Chauhan et al, 2010) and OTA in grapes (Battilani and Camardo Leggieri, 2015a).…”
Section: Mycotoxins and Producing Fungimentioning
confidence: 99%
“…Due to the annual and climatic variation of AFB 1 contamination level, it is necessary to build a prediction model by developing a continuous and effective AFB 1 monitoring program for pre-harvest peanuts during its growing season. Up to now, there had been some progress on model building in Australia and USA [28,29].…”
Section: Relationship Between Afb 1 Contamination Levels In Peanuts Amentioning
confidence: 99%
“…Until now, a lot of researches indicated that key environmental factors including temperature, humidity and precipitation significantly influenced fungus growth, infection as well as aflatoxin production [30][31][32]. And some efforts have been devoted to developing models to predict aflatoxin contamination in peanuts and maize with climatic data used as the main or only input, such as the Agricultural Production Systems Simulator (APSIM) and the CSM-CROPGRO-Peanut model [29,33]. However, few models were actually applied to the field to predict the future aflatoxin risk or just a small region for validation and demonstration.…”
Section: Building An Early Predictive Model Of Aflatoxin By Combiningmentioning
confidence: 99%
“…Cole et al (1985) noted that geocarposphere temperatures averaging 26.3 to 29.6 C were most conducive to aflatoxin accumulation in peanuts, while temperatures above 31.3 C appeared suppressive. These studies and others provided the information that Chauhan et al (2010) built into a simulation model that calculates the risk of aflatoxin contamination in peanuts. While this simulation has been shown to be reliable, its use may be limited due its complexity and the need for multiple environmental variable inputs.…”
mentioning
confidence: 99%